Untapped Resources or Deficient ‘Foreigners’ : Students of Vietnamese Background in Icelandic Upper Secondary Schools - Anh-Dao Tran 1959- (2015)
As Iceland’s population becomes more diverse, so does the student body in upper secondary schools. A number of studies during the past decade reported a high drop-out rate among immigrant students. The basic reasons students cited were low proficiency in the Icelandic language, low self-esteem, lack of motivation, and social isolation. Based on these findings, I ask how these phenomena can be explained by the theory and practice of multicultural education. The study applies the critical perspective to scrutinize the discourse of policy documents, their recontextualization in the schools and the students of Vietnamese background’s experiences. The philosophy of multicultural education is one of inclusion, insistence upon valuing diversity and equal opportunity regardless of gender, religion, and belief, ethnicity, race, socioeconomic status, disability or any other status (Banks, 2007b). In order to bring about equity in education that facilitates academic success for students of foreign background, multicultural education insists on the need of schools to be reformed and new pedagogy adopted (Gaine 2005; Banks 2004; Gay, 2000; Nieto, 2000). Grounded in multicultural education theories, this study’s purpose is to understand the implications of the concept of equality and how well the Icelandic educational system has established itself to make it equitable for young people of ethnic minority background. The methodology of the study draws upon critical ethnography, which was employed as an analytical tool to scrutinize the policy documents and analyze the interviews with administrators, teachers and students. The results reveal three basic conclusions. First, while acknowled-ging to some extent that Iceland is a multicultural society, the acts, regulations and curriculum that form the basis for teaching and inte-grating students of immigrant background, focus more on their deficit in Icelandic and assumed cultural deficiency instead of their own knowledge and culture that can enhance and facilitate their learning. ...